Kualitas Produk dan Promosi Penjualan terhadap Proses Keputusan Pembelian Van Java Chocolate Ginger di PT Tama Cokelat Indonesia - Nizar Alam Hamdani (Fakultas Ekonomi Universitas Garut, 2018)
This study consists of three variables, namely, the variable Product Quality, Sales Promotion and the Purchase Decision Process. In general, the purpose of this study is to determine the Effect of Product Quality and Sales Promotion on the Purchasing Decision Process at PT. Tama Chocolate Indonesia. The subjects in this study were consumers who had bought Van Java Chocolate Ginger at PT. Tama Chocolate Indonesia. Based on the problems and objectives of the study, the researcher formulated a hypothesis, namely: there is an influence between product quality and sales promotion on the purchasing decision process of Van Java Chocolate Ginger at PT. Tama Cokelat Indonesia. The method used in this research is descriptive and associative methods. The population in this study is not known with certainty, so to determine the size of the sample is using the Non Probability Sampling Technique with purposive sampling. So in this study, a sample of 96 people was obtained. In addition, based on data analysis, it was found that all instruments used in this study were declared valid and reliable. Furthermore, for the research results, the calculation with the simultaneous significance test (f test) shows that there is a significant influence on product quality and sales promotion on the purchasing decision process of Van Java Chocolate Ginger at PT. Tama Chocolate Indonesia.